Smart coating in protective clothing for firefighters: An overview and recent improvements. Issue 5 (June 2022) - Shakeriaski, Farshad; Ghodrat, Maryam; Rashidi, Maria; Samali, Bijan
Recently, new developments in the design and performance optimization of smart mechanisms associated with natural and man-made hazards have progressed considerably. This is mainly owing to advances in smart sensing mechanisms including communication and data technologies. This work provides a detailed overview of existing improvements on smart hazard monitoring equipment and materials applied in textile sensing systems. Given that fire is one of the most common disasters in many countries such as Australia, and every year many firefighters are affected by these unfortunate incidents, the focus of this study is on firefighters' protective clothing Fire Fighter Protective clothing. This review provides a unique opportunity to study smart sensing systems in coating technologies, potentially provides more effective techniques for training and better safety protocols of fire fighters. It aims to revisit the existing advances and address recent challenges and opportunities for improvement in the domain of smart coating and fire protective wearables. The goal of this review is to provide information about smart coating in protective clothing for firefighters. The capability of some of these clothing in managing thermal stresses, responding to humid environment, monitoring some critical parameters and adapting to the size of the wearers (clothes fabricated with phase change and shape memory substances) made them attractive choice in adjusting specific design features of industrial textiles. Various types of phase change and shape memory substances are defined and a combination of these substances within the structure of fabrics are presented. This paper also provides a detailed review on the heat exposure and capability of the shape memory substances (SMM) and phase change materials (PCM) to delay the heat transfer through fire fighter protective clothing. Referring to the former research, several issues have been detected using such substances. For instance, combination of phase change and shape memory materials needs fundamental improvements with regards to assessment techniques and testing criteria. Additionally, recent improvements in the domain of PCM and SMM including modifying mechanical features, functionality, and durability under different conditions have been informed. It has been suggested that the major problem in developing fabric-Phase Change Materials (PCMs) and Shape memory material (SMM) systems is their usage methods. At last recent developments on wearable monitoring systems applied in the firefighters' protective gear. Wearable sensors are usually used directly on the body or located on wearable items to monitor information related to firefighters' safety.